Vulnerabilities of GSM and Wiretapping - A. V. Novitskiy; D. M. Mikhailov; A. V. Starikovskiy; A. V. Zuykov (Безопасность информационных технологий, 2012)
The article presents the main methods used by hackers to listen to telephone conversations of subscribers and also offers ways to protect against them. The authors justify the necessity of developing a trusted operating system that implements a given security measures.